The community engagement course and action network: strengthening community and academic research partnerships to advance health equity - Akintobi, Tabia Henry; Barrett, R.; Hoffman, L.; Scott, S.; Davis, K.; Jones, T.; Brown, N. De Veauuse; Fraire, M.; Fraire, R.; Garner, J.; Gruner, A.; Hill, J.; et al. (Frontiers in Public Health, 2023)
Background: Historically Black Colleges and Universities and Minority Serving Institutions are uniquely positioned to implement community-campus research partnerships based on a history of service, the pursuit of community trustworthiness and student demographics often similar to surrounding marginalized communities .The Morehouse School of Medicine Prevention Research Center collaborates with members of Historically Black Colleges and Universities, Minority Serving Institutes, and community organizations on the Community Engaged Course and Action Network. This network is the first of its kind and aims to strengthen members’ ability to implement Community-Based Participatory Research (CBPR) principles and partnerships. Projects address public health priorities including mental health among communities of color, zoonotic disease prevention, and urban food deserts. Methods & Materials: To assess the effectiveness of the network, a Participatory Evaluation framework was implemented to conduct process evaluation which included review of partnership structures, operations, project implementation processes, and preliminary outcomes of the research collaborations. A focus group of Community Engagement Course and Action Network members (community and academic) was also conducted to identify benefits and challenges of the network with emphasis on key areas for improvement to further enhance the relationships between partners and to facilitate their subsequent community-campus research. Results: Network improvements were tied to themes strengthening community-academic partnerships including sharing and fellowship, coalition building and collaboration, and greater connections and awareness of community needs through their current community-academic partnerships. The need to conduct ongoing evaluation during and after implementation, for determining the early adoption of CBPR approaches was also identified. Conclusions: Evaluation of the network’s processes, infrastructure, and operation provides early lessons learned to strengthen the network. Ongoing assessment is also essential for ensuring continuous quality improvement across partnerships such as determining CBPR fidelity, assessing partnership synergy, and dynamics, and for quality improvement of research protocol. The implications and potential for advancing implementation science through this and similar networks are great towards advancing leadership in modeling how foundations in community service can advance to CBPR partnership formation and ultimately, health equity approaches, that are local defined and assessed.